Emotional intelligence among primary school teachers in relation to gender, teaching experience and type of school - Abd Karim, Aishah Hanim; Kamaruzaman, Mohd Hasyrie Rusydi (MNNF Publisher, 2025)
Teachers in Malaysia face increasing emotional demands, making emotional intelligence (EI) essential for sustaining well-being and teaching effectiveness. This study examines EI levels among primary school teachers in Putrajaya, focusing on gender, teaching experience, and type of school (national vs. international). A quantitative survey design was employed, using the Wong and Law Emotional Intelligence Scale (WLEIS) to measure four EI dimensions: self-emotion appraisal, others’ emotion appraisal, use of emotion, and regulation of emotion. Data were collected through an online survey of 67 teachers, and analyzed using descriptive statistics and independent samples t-tests in SPSS. Findings indicate that both male and female teachers reported high EI, with males scoring slightly higher in self-emotion appraisal and regulation, while females excelled in the use of emotion. Teachers with more than five years of experience recorded significantly higher EI than their less experienced peers, particularly in self-emotion appraisal and use of emotion. Furthermore, national school teachers demonstrated higher EI compared to international school teachers, especially in the use and regulation of emotion. These results highlight the importance of teaching experience and school context in shaping EI. From an Islamic perspective, EI aligns with values such as patience (sabr), compassion (rahmah), and God-consciousness (taqwa), emphasizing its role in holistic teacher development. The study suggests integrating EI into teacher education and professional development programs to strengthen resilience, enhance instructional quality, and improve student outcomes.